Pengembangan Aplikasi Media Graha Pancasila Untuk Pembelajaran PPKn Kelas X SMA Semester Ganjil - Sinta Yuliani (Civic-Culture : Jurnal Ilmu Pendidikan PKN dan Sosial Budaya, 2023)
Based on the results of interviews with Civics teachers at SMAN I Blitar, SMAN 3 Blitar, and SMAN 4 Blitar, there are obstacles experienced by teachers during the learning process, namely the lack of student enthusiasm, there are active students who always pay attention to the teacher, there are also passive students who are indifferent to learning. This has an impact on learning outcomes as well as student understanding of the material The results of distributing student needs questionnaires show that students are more interested in using android-based learning media. This research aims to find out the development of Graha Pancasila media in Civics class X SMA semester ganil and find out the teacher's readability of Graha Pancasila media. This research. is a Design and Development. on. this. development. is. limited. to. the. Zth. stage. i.e. product revision and. uses. a. quantitative. description. approach. The research subjects were Civics teachers and grade X students at SMAN 1 Blitar City in the 2022/2023 academic year. Data collection techniques using questionnaire distribution and..wavaucara Researchers. develop learning media in the form of applications in which there are. material, learning videos, problem analysis quizzes and money disks, Based on the results of the study showed that the student readability test was 04% and the guu readability ji was 88% including in the range>81% with "very good" criteria, atina Graha Pancasila learning media has reached the criteria readable.